Quasi-Developable and Signed Multi-Strip Approximation of a Freeform Surface Mesh for Efficient Flank Milling. (November 2021) - He, Dong; Li, Zhaoyu; Li, Yamin; Tang, Kai
Abstract: Five-axis flank milling is widely used due to its higher cutting efficiency and better surface finish quality compared with point milling. In recent years, the use of flank milling has been further extended from single-pass milling to multi-pass milling. However, the existing multi-pass flank milling methods focus only on a simple parametric surface and suffer from extraneous machining problems due to the varied cutting width. Moreover, as they ignore the tool's effective cutting length, they are in general incapable of handling other related constraints such as the hard constraints of no-overcut and interference-free. In this paper, we propose a new algorithm of planning multi-pass flank milling for a complex freeform surface mesh. In our method, the design surface mesh is naturally partitioned based on a tangent vector field and each partitioned patch is approximated by a set of piecewise quasi-developable quad strips, on which semi-finishing flank milling tool paths of a given constant cutting width are generated tending to all the required constraints such as no-overcut. The powerful algebraic technique of level-set method is utilized to generate a scalar field on each patch whose iso-lines will serve as the equi-distant cutter contact rulings of the initial quad strips. An elaborated energy-based unified framework is then presented that will optimize the signed quad strips to increase their developability while satisfying all the machining constraints, thus further reducing the flanking machining error with all the hard constraints (e.g., no-overcut) upheld. Ample physical cutting experiments are performed, whose results convincingly confirm the advantages of the proposed method. Highlights: A new multi-pass flank milling method for complex freeform surface mesh is proposed. The design surface mesh is partitioned based on a tangent vector field. Each partitioned patch is approximated by a set of signed quasi-developable quad strips. The tool paths are generated on the strips tending to the machining constraints. Simulations and experiments have verified the effectiveness of our method.